Bilateral Unusual Course of the Median Nerve, Variation in Branching Pattern of the Brachial and Superficial Ulnar Arteries: A Rare Case Report of Multiple Neuroarterial Variation - Ahmadpour, Shahriar; Foghi, Khadijeh (Journal of Morphological Sciences, 2019)
Introduction Bilateral unusual course of the median nerve accompanied with variations of the brachial artery branching pattern are uncommon.Materials and Methods During the routine educational dissection of an upper limb, an interesting neurovascular variation was found in a 45-year-old male cadaver.Results We found a bilateral unusual and variant course of the median nerve in the arm region. The right median nerve, after formation, descended from the medial to the brachial artery, crossed the brachial artery anteriorly from medial to lateral, then inferiorly and lied medially to the distal third of the brachial artery, while the left median nerve ran medial to the brachial artery, passing anteriorly from medial to lateral, and, at the distal end of the arm, it buried itself in the brachialis muscle. Another set of findings were absence of the superior and inferior ulnar collateral arteries, superficial ulnar artery in the forearm and common interosseus artery originated from radial artery.Conclusion These types of compound neurovascular variations are of great importance in orthopedic, vascular, reconstructive surgeries and even in routine nursing care.
Keywords: anatomical variations; median nerve; ulnar artery; ulnar collateral arteries; common interosseous artery; cadaver